Mapping the Mechanical Properties of Hierarchical Supercrystalline Ceramic-Organic Nanocomposites - Bor, Büsra (Molecules, 2020)
Multiscale ceramic-organic supercrystalline nanocomposites with two levels of hierarchy have been developed via self-assembly with tailored content of the organic phase. These nanocomposites consist of organically functionalized ceramic nanoparticles forming supercrystalline micron-sized grains, which are in turn embedded in an organic-rich matrix. By applying an additional heat treatment step at mild temperatures (250–350 °C), the mechanical properties of the hierarchical nanocomposites are here enhanced. The heat treatment leads to partial removal and crosslinking of the organic phase, minimizing the volume occupied by the nanocomposites’ soft phase and triggering the formation of covalent bonds through the organic ligands interfacing the ceramic nanoparticles. Elastic modulus and hardness up to 45 and 2.5 GPa are attained, while the hierarchical microstructure is preserved. The presence of an organic phase between the supercrystalline grains provides a toughening effect, by curbing indentation-induced cracks. A mapping of the nanocomposites’ mechanical properties reveals the presence of multiple microstructural features and how they evolve with heat treatment temperature. A comparison with non-hierarchical, homogeneous supercrystalline nanocomposites with lower organic content confirms how the hierarchy-inducing organic excess results in toughening, while maintaining the beneficial effects of crosslinking on the materials’ stiffness and hardness.